2013
DOI: 10.1136/jech-2013-203098.7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Telephone Support Interventions on Coronary Artery Disease (Cad) Patient Outcomes During Cardiac Rehabilitation: A Systematic Review and Meta-Analysis

Abstract: Background: Cardiac rehabilitation is offered to individuals after cardiac events to aid recovery and reduce the likelihood of further cardiac illness. However, patient participation remains suboptimal and the provision of high quality care to an expanding population of patients with chronic heart conditions is becoming increasingly difficult. A systematic review and meta-analysis was conducted to determine the effect of telephone support interventions compared with standard postdischarge care on coronary arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…Telephone support can help provide specialized preventive care to patients with more difficult access to services, and has the potential of some reduction of the health system burden. This is an important aspect for investigation in future research (18) .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Telephone support can help provide specialized preventive care to patients with more difficult access to services, and has the potential of some reduction of the health system burden. This is an important aspect for investigation in future research (18) .…”
Section: Discussionmentioning
confidence: 98%
“…A recent meta-analysis on the effects of telephone follow-up on the rehabilitation of patients with CAD has shown evidence that support provided by telephone follow-up may lead to anxiety reduction (18) . The study highlighted the need for follow-up studies for periods of 12 months or more, and by taking into account there are important benefits in reducing anxiety, which may contribute to the reduction of cardiac risk and hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 describes the diversity of the participants enrolled in the program. Table 2 [11,12]. This multidisciplinary approach is the basis for the PCMH model promoted by the Agency for…”
Section: Methodsmentioning
confidence: 99%
“…Studies were able to demonstrate similar significant improvements in exercise capacity in home-based CR as that of the center-based CR programs. 42,43 A recent systematic review and meta-analysis, 52 however, showed that telephone-supported CR interventions for coronary heart disease patients was limited to reducing certain risk factors such as anxiety and depression, while improving systolic BP and the likelihood of smoking cessation. Furthermore, telephone-supported CR interventions also have their drawbacks, as possible labor-intensive conversations are expensive; this is supported by less conclusive cost-effectiveness reports of such programs than by reports that are focused on clinical effectiveness.…”
Section: Cardiac Rehabilitation With Telephone Supportmentioning
confidence: 99%